Sustainable companies in Mexico and their relationship with water. A look from the 2030 Agenda (Management Challenges, 2023)
Objective: Analyze goals and actions that sustainable companies listed on the Mexican Stock Exchange implement for the care and conservation of water in search of compliance with the Sustainable Development Goals.Methods and techniques: 29 so-called sustainable companies listed on the Mexican Stock Exchange with the S&P/BMV Total Mexico ESG Index are studied. The investigation is developed in 5 stages. Documentary analysis is applied as a data collection technique and data record cards are used. The sources of information are the sustainability reports of each company for the years 2017, 2018 and 2019. The data obtained is processed and presented through Lucidchart and Microsoft Excel.Results: It is identified that sustainable companies in Mexico promote responsible water saving through initiatives that contribute to the care and conservation of the vital liquid, these practices show that in the Mexican business sector there is progress in meeting the objectives of the 2030 Agenda.Conclusions: The commitment to the environment is the responsibility of the State, society and the business sector, the latter, regardless of the size of the organization, must contribute to guaranteeing that future generations have natural resources to satisfy their needs. Sustainable companies in Mexico, their goals and actions in matters of water care and conservation are aligned with the objectives of sustainable development, being an important step towards a society committed to natural resources.